EXPLORING THE MODERATING ROLE OF PUBLIC SERVICE MOTIVATION ON THE EFFECT OF PERSON-ENVIRONMENT FIT ON INDIVIDUAL PERFORMANCE: A CASE STUDY AMONG PUBLIC SERVANTS IN SELANGOR - Ayu Kamareenna Abdullah Thani; Nurhidayah Rosely; Siti Nur Zahirah Omar (International Journal of Accounting, Finance and Business, 2024)
An individual's performance is assessed based on their contribution towards achieving a specific target, whereas the performance of a public organization is evaluated based on the goals it has accomplished in alignment with its purpose statements. Positive individual behavior plays a crucial role in determining positive life outcomes, including the development of strong professional ethics. Individuals who possess a strong alignment between their psychological (spiritual) and physical (physical) functions play a significant role in determining their effectiveness in the organization This study investigates the effects of person-environment fit, specifically person-job fit and person-organization fit, on the individual performance of public sector servants in Malaysia. This study underwent testing using SPSS on a sample of 384 individuals employed in the public sector in Selangor. The presence of both person-job fit and person-organization fit has a favorable impact on individual performance. Moreover, the influence of Public Service Motivation on the connection between person-job fit person-organization fit, and individual performance is statistically significant. Therefore, it is crucial to devise strategies and establish appropriate organizational settings to effectively enhance the performance levels of public sector employees.